Effect of the Site of Infection Source and Some Onion Genotypes on Management of Onion Yellow Dwarf Virus in the River Nile State, Sudan - Hamad, Abdelmagid Adlan; Nouri, Abdalla Hussein (University of Khartoum Journal of Agricultural Sciences, 2023)
Field experiments were carried out at Hudeiba Research Station Farm during 2004/ 05 and 2005/06 seasons to evaluate the effect of the location of infection source on the spread of onion yellow dwarf virus (OYDV) and to screen 18 onion genotypes for resistance to the virus. Disease incidence was assessed in blocks of 60 x 6 m planted with disease-free onion seedlings and located upwind and downwind of the disease source at distances of 0, 6, 12, 18, 24 and 30 m. Average incidence of 33.7% and 57.8% was recorded in downwind blocks compared to 8.0% and 9.9% in upwind blocks, irrespective of the distance from the disease source, in 2004/05 and 2005/06, respectively. The blocks located downwind and adjacent to the disease source had the highest disease incidence of 93.4% and 95.5% compared with 7.8% and 18.9% in blocks located at a distance of 30 m away from the source during the two seasons, respectively. In upwind blocks, disease incidence of 15.4% and 20.2% was recorded in blocks adjoining the disease source, while incidence of 3.7% and 4.85% was recorded in blocks located at a distance of 30 m in the two seasons, respectively. None of the genotypes tested was resistant to the OYDV infection; however, Baftaim Red genotype proved to be tolerant to the virus.